Well-formed defeat paths in abstract argumentation frameworks - Martínez, Diego C. (2005)
Abstract argumentation systems are formalisms for argumentation where some components remains unspecified, usually the structure of arguments. In the dialectical process carried out to identify accepted arguments in the system, some controversial situations may be found, related to the reintroduction of arguments in this process, causing a circularity that must be treated in order to avoid an infinite analysis. Some systems apply a single restriction to argumentation lines: no previously considered argument is reintroduced in the process. In this work we show that a more specific restriction need to be applied, taking subarguments into account. We finally present a new definition of acceptable argumentation lines